High strain rate behavior of nanocomposites and nanocoatings - Jindal, Prashant (SpringerBriefs in Materials,, 2015)
This book describes the use of multiwall carbon nanotubes as composites with polycarbonates and as protective coatings on glass surfaces. The book explains fabrication and characterization methods for these composites and coatings.  The author reports on the use of Split Hopkinson Pressure Bar set up for evaluating the dynamic strength of these composites and coatings and studying the role of carbon nanotubes in the enhancement of their dynamic strength.<.